Effect of amlodipine and L-carnitine on bone metabolism in ovariectomized rats - Ahmed F.A Ghany; Yasser M Ashour; Nawal B Aly; Lobna A Abdelzaher; Ahmed S Mahmoud (Wolters Kluwer Medknow Publications, 2021)
Background Amlodipine as a calcium channel blocker has anti-inflammatory effect through overaugmentation of nitric oxide production and antioxidant effect by reduced superoxide radicals and increased level of superoxide dismutase. l-carnitine has anti-inflammatory action through reaction with acyl group that is accumulated in anoxic cells and antioxidant effect through decreasing the superoxide anion production. Aim The aim was to evaluate the possible ameliorating effect of amlodipine (AML) and L-Carnitine (L-C) combination on osteoporotic bony changes in ovariectomized (OVX) rats versus each drug separately. A total of 50 adult female albino rats (weighting 100-125 g) of local strain were chosen as an animal model for this study. The animals were randomly divided into five groups. Each group comprised ten rats: group 1, negative control; group 2, OVX rats, positive control; group 3, AML-treated OVX rats; group 4, L-C-treated OVX rats, and group 5, AML and L-C-treated OVX rats. Bony changes were examined through evaluating markers of bone turnover, such as alkaline phosphatase and osteocalcin; femoral metaphyseal histomorphology; and serum proinflammatory cytokines, such as tumor necrosis factor-α, expression. Results alkaline phosphatase, osteocalcin, and tumor necrosis factor-α were significantly elevated in positive control group, which was associated with marked deterioration of bone microarchitecture. Treatment with AML and L-C combination significantly mitigated inflammation and histopathological osteoporotic changes compared with each of AML and L-C drugs separately. Conclusion AML and L-C combination could have a synergistic role in management of radical osteoporosis in OVX rats over each drug separately.